Data‐driven respiratory signal estimation from temporally finely sampled projection data in conventional cardiac perfusion SPECT imaging. Issue 1 (13th December 2021) - Pretorius, P. Hendrik; King, Michael A.
Abstract: Purpose: The aim of this work was to revisit the data‐driven approach of axial center‐of‐mass (COM) measurements to recover a surrogate respiratory signal from finely sampled (100 ms) single photon emission computed tomography (SPECT) projection data derived from list‐mode acquisitions. Methods: For our initial evaluation, we acquired list‐mode projection data from an anthropomorphic cardiac phantom mounted on a Quasar respiratory motion platform simulating 15 mm amplitude respiratory motion. We also selected 302 consecutive patients (138 males, 164 females) with list‐mode acquisitions, external respiratory motion tracking, and written consent to evaluate the clinical efficacy of our data‐driven approach. Linear regression, Pearson's correlation coefficient ( r ), and standard error of the estimates (SEE) between the respiratory signals obtained with a visual tracking system (VTS) and COM measurements were calculated for individual projection data sets and for the patient group as a whole. Both the VTS‐ and COM‐derived respiratory signals were used to estimate and correct respiratory motion. The reconstruction for six‐degree of freedom rigid‐body motion estimation was done in two ways: (1) using three iterations of ordered‐subsets expectation‐maximization (OSEM) with four subsets (16 projection angles per subset), or 12 iterations of maximum‐likelihood expectation‐maximization (MLEM). Respiratory motion compensation was done employing either OSEM with 16 subsets (four projection angles per subset) and five iterations or MLEM and 80 iterations, using the two respiratory estimates, respectively. Polar map quantification was also performed, calculating the percentage count difference (%Diff) between polar maps without and with respiratory motion included. Average % Diff was calculated in 17 segments (defined according to ASNC Guidelines). Paired t ‐tests were used to determine significance ( p ‐values). Results: The r ‐value calculated when comparing the VTS and COM respiratory signals varied widely between −0.01 and 0.96 with an average of 0.70, while the SEE varied between 0.80 and 6.48 mm with an average of 2.05 mm for our patient set, while the same values for the one anthropomorphic phantom acquisition are 0.91 and 1.11 mm, respectively. A comparison between the respiratory motion estimates for VTS and COM in the S‐I direction yielded an r = 0.90 (0.94), and an SEE of 1.56 mm (1.20 mm) for OSEM (MLEM), respectively. Bland–Altman plots and calculated intraclass correlation coefficients also showed excellent agreement between the VTS and COM respiratory motion estimates. Average S‐I respiratory estimates for the VTS (COM) were 9.04 (9.2 mm) and 9.01 mm (9.14 mm) for the OSEM and MLEM, respectively. The paired t ‐test approached significance when comparing VTS and COM estimated respiratory signals with p ‐values of 0.069 and 0.051 for OSEM and MLEM. The respiratory estimates from the anthropomorphic cardiac phantom experiment using the VTS (COM) were 12.62 (14.10 mm) and 12.55 mm (14.29 mm) for OSEM and MLEM, respectively. Polar map quantification yielded average % Diff consistently better when employing VTS‐derived respiratory estimates to correct for respiration compared to the COM‐derived estimates. Conclusions: The results indicate that our COM method has the potential to provide an automated data‐driven correction of cardiac respiratory motion without the drawbacks of our VTS methodology. However, it is not generally equivalent to the VTS method in extent of correction.